Visual Acuity, Quality of Life and Visual Function Outcomes after Cataract Surgery in Bali. (August 2015) - Farmer, Lachlan; Innes-Wong, Cecilia; Bergman-Hart, Caroline; Casson, Robert J.; Crompton, John
Abstract Purpose: To assess post-cataract surgery intermediate-term (>6 months) data of visual acuity (VA), surgical complications, refractive outcomes, quality of life (QOL) and visual function (VF) from a non-governmental organization program in Indonesia. Methods: Retrospective cohort study design. Participants were a selection of patients who underwent cataract surgery by the John Fawcett Foundation between 2006 and 2011, with at least 6 months follow-up. Patients underwent comprehensive ophthalmic examinations. QOL and VF questionnaires were administered. Results: From a total of 1557 invited to attend, 547 patients participated; 99.8% of eyes had presenting VA <6/60. At day 1 postoperatively, 52.1% of patients had a good outcome by World Health Organization criteria (unaided VA ≥ 6/18). Six months or later postoperatively, 85% of eyes had best-corrected VA ≥ 6/18 and 5.6% of eyes had best-corrected VA < 3/60. At final follow-up, mean postoperative spherical equivalent refraction was −2.35 diopters (standard deviation 1.75, n = 542). On a scale of 1–100, median converted values for QOL were 25.0 preoperatively and 74.0 postoperatively, a statistically significant improvement (p < 0.001). Of eyes with VA better than 3/60 on postoperative day 1, 5.7% (95% confidence interval 3.6–7.9%) became blind (VA < 3/60) at the 6-month or later time point. Conclusion: Cataract surgery in this population markedly improved QOL, despite a trend towards myopic refractive outcomes. These findings raise questions about biometric methodology, intraocular lens power calculations and refractive targets. Postoperative day 1 VA data may be a reasonable proxy of the intermediate-term rate of non-blind eyes.